A vascular endothelial growth factor deficiency characterises scleroderma lung disease. Issue 9 (8th March 2012) - De Santis, Maria; Bosello, Silvia Laura; Capoluongo, Ettore; Inzitari, Rosanna; Peluso, Giusy; Lulli, Paola; Zizzo, Gaetano; Bocci, Mario; Tolusso, Barbara; Zuppi, Cecilia; Castagnola, Massimo; Ferraccioli, Gianfranco
Abstract : Objectives: Vascular endothelial growth factor (VEGF) is thought to play an important role in systemic sclerosis (SSc) pathogenesis. It was found to be upregulated in the serum and in the affected skin of scleroderma patients. However, its involvement in scleroderma lung disease is not clear. This study aimed to evaluate VEGF concentration in the bronchoalveolar lavage fluid (BALF) of scleroderma patients with interstitial lung disease, to correlate the cytokine levels in plasma and in the lung with pulmonary functional, radiological and cellular parameters, and with the progression of lung disease. Methods: BALF and plasma VEGF concentrations were analysed by ELISA in 55 SSc patients with lung disease and 17 controls. Cytokine real-time PCR messenger RNA expression in alveolar macrophages was assessed. Lung involvement progression was evaluated after a 1-year follow-up. Results: VEGF was found to be significantly lower in the BALF of scleroderma patients compared with controls. The lowest concentrations were observed in SSc patients with alveolitis. A decreased VEGF expression in alveolar macrophages was found in SSc patients with alveolitis. VEGF concentration in BALF correlated inversely with the ground glass score on high-resolution CT and with BALF neutrophil cell count. Moreover, SSc patients with a lower VEGF concentration showed a worsening in the interstitial score at follow-up. Conclusions: Scleroderma interstitial lung disease is characterised by a VEGF deficiency. Lower concentrations were found in patients with progression of lung disease.